IDENTIFICATION OF POST-TRAUMIC STRESS DISORDER IN CHILDREN AFTER THE FLOOD DISASTER IN SOUTHEAST ACEH DISTRICT - Derita Perhatian (CV Naskah Aceh, 2026)
Flood disasters have a significant impact on human life, both physically and psychologically. Children are a vulnerable group at higher risk during and after a disaster. The most common psychological effect after a disaster is Post Traumatic Stress Disorder (PTSD). The purpose of this study was to detect PTSD early in children who were victims of flood disasters. This study used a quantitative design with a cross-sectional approach . A total of 61 child flood victims were involved in the study. The study was conducted in Southeast Aceh Regency, one of the worst flood locations in Aceh Province in 2025. The instrument used was the PTSD Checklist for DSM-5 (PCL-5), which consists of 20 questions. The results showed that 39.3% of children experienced PTSD, while 60.7% did not experience PTSD. The incidence of PTSD increased from one week after the disaster, characterized by symptoms of re-experiencing the traumatic experience, avoidance, negative changes in mood and cognition, and hyperarousal. Age, gender, and level of exposure also risk factors influence the emergence of PTSD in children. It is recommended that health workers provide immediate treatment to child victims of disasters.